Research on Battery Management System with Dual-branch Redundancy - YANG Jiejun; LIU Yuan; WEN Jianfeng; HUANG Hao (Kongzhi Yu Xinxi Jishu)
In view of redundant design of power battery pack and high pressure safety of hybrid locomotive, taking battery management system (BMS) of hybrid locomotive power battery pack as research object, a BMS redundancy design scheme with dual branches and boards was presented and the feasibility of the system was verified by charge-discharge test of vehicle. The results show that in addition to the fact that the dual-branch BMS can monitor battery pack status information in real time during normal operation, the proposed scheme can also realize normal operation of another branch BMS when the battery system of one branch or BMS fails, the safety of the vehicle is guaranteed and the correctness of the scheme is verified.